Importance Of Fecoliths In The Etiology Of Acute Appendicitis - Dr. BHUSHAN M; Dr. B Jeevan Kumar; Dr. HARINI V; Dr. B.M. Praveen Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Among all the causes for the acute appendicitis, the predominant predisposing factor is the change in the diet of the individual. With the modernization and industrialization, more and more people have been adopting a way of life mimicking the western population. The change in the way of life, the effect of the western culture on the eastern population has led to a lot of changes in their diet and is the leading cause behind predisposition to appendicitis. Patient diagnosed with acute appendicitis which includes clinical and radiological were chosen. The patients were briefed regarding the study methodology and the purpose of the study. Those willing underwent a detailed evaluation after taking a written consent. The following routine pre-operative investigations were noted-Hemoglobin (g/dL), Total counts, Differential counts, ESR, S. albumin. we noted that the 1.30% had an engorged appendix, 7.30% had an appendix with an inflamed base , 10.70% had an engorged appendix inflamed tip , in 74.70% the appendix was inflamed in its whole length, 0.70% had an appendix with an inflamed whole length, perforation , 1.30% had an appendix with an inflamed in its whole length with free fluid , 1.30% had an appendix with a minimal inflammation and 1.30% had an perforated appendix.